PENGARUH KEPEMIMPINAN ETIKAL, KOMITMEN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Balthasar Watunglawar; Katarina Leba (LPPM Politeknik Saint Paul Sorong, 2020)
The purpose of this paper is to describe and analyze the influence of ethical leadership, organizational commitment, and job satisfaction on employee performance. To achieve these objectives, this study uses quantitative research methods. Data were collected through questionnaires and documentation of 38 respondents in Sorong City BKPSDM analyzed using SPSS 22. The results showed that there was a significant influence between ethical leadership, organizational commitment, and job satisfaction on employee performance. So to improve employee performance, the organization and institutional management must pay attention to improving the quality of leadership, organizational commitment, and job satisfaction. The findings of this study are expected to be useful for further researchers in the fields of management, accounting, administration and economics.